Value chain on industrial agroforestry in Tamil Nadu for sustaining raw material security and mitigating climate change - Parthiban, K T (Indian Farming, 2020)
The growing demand for wood and wood products and reducing supply from natural forests coupled with unorganised supply chain have demanded sustainability plan to ensure raw material security and to stabilize the ecosystem and the environment. The existing agro and plantation forestry developments have experienced wide range of constraints and problem from the entire value chain to consumption system. Hence, a value chain model has been designed exclusively for industrial agroforestry and resolved the issues through technological, organisational and marketing interventions. The development and deployment of HYSR clones, precision silviculture and multifunctional agroforestry have increased the productivity and enhanced the profitability which attracted several farmers towards tree husbandry in farmlands. To sustain these value chain systems, an Institution called Consortium of Industrial Agroforestry has been established and linked all stakeholders involved in the entire Production to Consumption System. Similarly, another institution called agroforestry business incubator has been established which caters to the need of skill development and involved in creation of start-ups, entrepreneurs and new industries which ensured sustainable income and employment generation opportunities. This model of Industrial Agroforestry value chain and the associated consortium and incubator development has a very good replication potential across India for productivity and profitability improvement besides acting as an alternate land use system for mitigating the growing concerns on climate change.